PERKAWINAN DIBAWAH UMUR DAN AKIBAT HUKUMNYA MENURUT UU PERKAWINAN - Lusia Indrastuti, Agatha Jumiati & (Adi Widya : Jurnal Pengabdian Masyarakat, 2017)
Community service aims to provide an understanding of underage marriage and legal consequences according to the Marriage Law. The target to be achieved in community service is its own community, especially for the mothers who are joined of the group PKK Desa Klegen Colomadu, Karanganyar regency. To achieve the objectives that have been set in the community service, the method used is a speech which followed by question and answer session.. The speaker seeks to present the legal counseling material in a straightforward and compelling way so that it is easier to understand. The atmosphere is made as comfortable as possible so that the participants do not hesitate or embarrassed to ask. Every question is always tried to be answered. After following this activity, the community is hoped to be more understand about underage marriage and its legal consequences as regulated in the Marriage Law.Keywords: Underage Marriage, Legal Effects and Marriage Law